Economic Development Matters: A Meta‐Regression Analysis on the Relation between Environmental Management and Financial Performance. (17th May 2017) - Hang, Markus; Geyer‐Klingeberg, Jerome; Rathgeber, Andreas; Stöckl, Stefan
Summary: Although the existing body of empirical literature on the relation between corporate environmental performance (CEP) and corporate financial performance (CFP) is continuously growing, results are still inconclusive about this fundamental question in industrial ecology. Comparisons are difficult because of various estimation methods as well as the overall heterogeneous and complex interaction between the two constructs, but especially because of country‐specific data sets. Consequently, we raise the question of whether regional differences are the driving force buried underneath the inconclusiveness. Therefore, the aim of this article is to explore this heterogeneity by aggregating 893 existing results from 142 empirical primary studies that are based on more than 750, 000 firm‐year observations. Our findings suggest a convex impact of a country's economic development on the magnitude of the CEP‐CFP effect (i.e., the effect is positive in developing countries, disappears in emerging countries, and is again positive in highly developed countries). We also find that the overall positive relation strengthens for market‐based CFP measures and diminishes for countries with civil law systems, firms from the service sector, reactive environmental activities, and process‐based CEP measures. Further, several aspects of the examined data sample and the inclusion of relevant control variables explain heterogeneity in previous research results.